Data-driven process discovery and analysis : 5th International Symposium, SIMPDA 2015, Vienna, Austria, December 9-11, 2015, Revised selected papers /: 5th International Symposium, SIMPDA 2015, Vienna, Austria, December 9-11, 2015, Revised selected papers. (2017) - Unknown
No abstract available